1981
DOI: 10.1002/j.1537-2197.1981.tb06354.x
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Low Molecular Weight and High Cysteine Containing Albumin Storage Proteins in Oilseeds of Diverse Species

Abstract: The proteins in the oilseeds of species from 11 families, including sunflower, mustard, linseed, almond, lupin, peanut, cucumber, Brazil nut, hazelnut, yucca, castor bean, and cottonseed were studied. Sucrose gradient centrifugation showed that a substantial proportion of the total seed protein from each species migrated with a 2S sedimentation coefficient. The 2S proteins, being water‐soluble and thus termed albumins, comprised 20–60% of the total seed proteins, while faster migrating globulins comprised the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
59
0
1

Year Published

1990
1990
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(63 citation statements)
references
References 20 publications
3
59
0
1
Order By: Relevance
“…As expected, the napin-type albumins (Figures 7B and 7D) were identified in the 2S fractions of the gradient, and the legumintype globulin ␣-and ␤-chains ( Figures 7B and 7C) represented the predominant polypeptides in the 12S fractions. Interestingly, in contrast to the seed protein sedimentation profiles of many other plant species but similar to those of Brassica spp (Youle and Huang, 1981), only very minor amounts of polypeptides were observed in the 7S fractions of the gradient. The ‫-52ف‬ to 30-kD polypeptides detected in these fractions ( Figure 7B, fractions 13 to 18; see also Figure 9A, lane 1) likely represent the previously identified processed N-and C-terminal chains of vicilin-like proteins (Gruis et al, 2002), which are minor storage proteins in Arabidopsis seeds (F. Gruis, unpublished data).…”
Section: Assembly Of Seed Proteins In Vpe Mutantsmentioning
confidence: 66%
“…As expected, the napin-type albumins (Figures 7B and 7D) were identified in the 2S fractions of the gradient, and the legumintype globulin ␣-and ␤-chains ( Figures 7B and 7C) represented the predominant polypeptides in the 12S fractions. Interestingly, in contrast to the seed protein sedimentation profiles of many other plant species but similar to those of Brassica spp (Youle and Huang, 1981), only very minor amounts of polypeptides were observed in the 7S fractions of the gradient. The ‫-52ف‬ to 30-kD polypeptides detected in these fractions ( Figure 7B, fractions 13 to 18; see also Figure 9A, lane 1) likely represent the previously identified processed N-and C-terminal chains of vicilin-like proteins (Gruis et al, 2002), which are minor storage proteins in Arabidopsis seeds (F. Gruis, unpublished data).…”
Section: Assembly Of Seed Proteins In Vpe Mutantsmentioning
confidence: 66%
“…The 2S albumins are small water soluble proteins found in a variety of plant species (Youle and Huang, 1981). Phylogenetic relationships have been established among 2S albumins found in different crucifers (Raynal et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Relatively little is known about the expression of 2S albumins in transgenic plants, although they constitute the most abundant class of seed storage proteins in many dicot plants (41). Also referred to as 1.7S albumins or napin-like proteins (8,41), they are water-soluble seed storage proteins, present in multiple isoforms and composed of two polypeptide chains of 8 to 12 and 3 to 5 kD, linked by disulfide bridges (2,16,23).…”
mentioning
confidence: 99%
“…Also referred to as 1.7S albumins or napin-like proteins (8,41), they are water-soluble seed storage proteins, present in multiple isoforms and composed of two polypeptide chains of 8 to 12 and 3 to 5 kD, linked by disulfide bridges (2,16,23). 2S albumin genes are encoded by multigene families (36) and are of particular interest because cDNA (1,8,13) and gene cloning experiments (23,30) have shown that the protein is formed from large precursors which undergo extensive proteolytic processing, including signal peptide cleavage, removal of an additional amino-terminal fragment as well as an internal segment, and elimination of a few carboxy-terminal residues (8,16).…”
mentioning
confidence: 99%